2020
DOI: 10.1002/solr.202000599
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylammonium: An A‐Site Cation for Modifying CsPbI3

Abstract: All-inorganic perovskite materials are attractive alternatives to organic-inorganic perovskites because of their potential for higher thermal stability. Although CsPbI 3 is compositionally stable under elevated temperatures, the cubic perovskite α-phase is thermodynamically stable only at >330 C and the low-temperature perovskite γ-phase is metastable and highly susceptible to nonperovskite δ-phase conversion in moisture. Many methods have been reported which show that the incorporation of acid (aqueous HI) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…A redshift in the PL emission has been observed in mixed‐cation Cs x [(CH 3 ) 2 NH 2 ] 1− x PbI 3 perovskites with increasing content of the larger (CH 3 ) 2 NH 2 + cation (when x ≤ 0.2) due to consequent changes in the crystal structure that increase orbital overlap between Pb and I atoms. [ 16 ] We note a secondary emission at 828 nm in the PL measurements when light is incident on the film and glass sides of the perovskite made on PEDOT:PSS between days 0–2 (Figure 2B). We believe this secondary emission stems from the self‐absorption of the primary emission as a result of internal reflections.…”
Section: Resultsmentioning
confidence: 99%
“…A redshift in the PL emission has been observed in mixed‐cation Cs x [(CH 3 ) 2 NH 2 ] 1− x PbI 3 perovskites with increasing content of the larger (CH 3 ) 2 NH 2 + cation (when x ≤ 0.2) due to consequent changes in the crystal structure that increase orbital overlap between Pb and I atoms. [ 16 ] We note a secondary emission at 828 nm in the PL measurements when light is incident on the film and glass sides of the perovskite made on PEDOT:PSS between days 0–2 (Figure 2B). We believe this secondary emission stems from the self‐absorption of the primary emission as a result of internal reflections.…”
Section: Resultsmentioning
confidence: 99%
“…Marshall and coworkers further explored and quantified the impact and limitations of the production method of DMA + partially replacing Cs + . 72 They found that the perovskite could form a stable phase only when 25% DMA + replaced Cs + . When the concentration of DMA + increased, significant phase separation (CsPbI 3 and DMAPbI 3 ) occurred.…”
Section: Strategies For Improving the Efficiency And Stability Of Csp...mentioning
confidence: 99%
“…[ 17 ] Snaith et al presented that DMA can successfully incorporate into the CsPbI 3 perovskite to form an alloyed composition of Cs x DMA 1− x PbI 3 , which is more stable under atmospheric conditions than original CsPbI 3 . [ 18 ] In such a broad research background, some publications have revealed that DMA can successfully incorporate in the CsPbI 3 films after mild annealing. However, there have been conflicting reports deem that it simply manipulates the crystallization process and then serves as a bystander in the final films.…”
Section: Introductionmentioning
confidence: 99%